Developing Biographical Texts by Audio-visual Teaching Materials: Animaker-Web for High School Students - Paino, Novhira Putri; Hutagalung , Trisnawati (Utamax : Journal of Ultimate Research and Trends in Education, 2022)
The development of Web-based platform in teaching English could help teachers to utilize technology in an effort to create more attractive teaching and learning process during online learning. This R&D study works on the development of biographical text materials using Animaker's web-assisted audio-visual teaching materials at the high school level. The frame development model proposed by Borg and Gall consists of 6 stages, namely Potential and Problems, Data Collection, Product Design, Product Validation, Product Revision, and Dissemination. The testing result of Animaker's web-assisted audio-visual teaching materials at the high school level shows an average score of 83.43% which indicates the Animaker-based audio-visual teaching materials are valid and feasible to use in High School Level. The average results of the feasibility assessment of operating audio-visual teaching materials with the aid of Animaker's web at the high school level based on the validator's perception, namely material experts 76.87% and design experts 90% fall into the criteria of good and very good. These results showed that Animaker web - assisted audio - visual teaching materials at the high school level can be used by teachers to create more creative atmosphere in the online class by utilizing technology to motivate and improve students' skills.